IDENTIFIKASI JENIS POHON FAMILI DIPTEROCARPACEAE DI KAWASAN ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA PONTIANAK - maria, karokak widiwati; manurung, togar fernando; sisillia, lolyta (JURNAL HUTAN LESTARI, 2016)
Dipterocarpaceae is one of trees that inhabits in Indonesia forest. Dipterocarpaceae has various types and is grouped in nine genus. The research work aimed to find out characteristics of morphology of Dipterocarpaceae in area of Arboretum Sylva University of Tanjungpura Pontianak. The research work employed exploration method by searching around types of ecosystem or types of vegetation of this plant. Based on identification finding, there were 31 species out of 6 genus of Dipterocarpaceae family. Shorea is genus that has the biggest number of species that is 24 species, while Cotylelobium and Hopea genus have 2 species, and Anisoptera, Dipterocarpus and Dryobalanops genus have 1 species. The data gathered in the field was vegetative characteristics